Frequency of Iron Deficiency in Females having Normal Haemoglobin level Complaining of Fatigue - Hafiza Sidra tul Muntaha; Afshan Noureen Arain; Muhammad Qasim Ali (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency is the most widespread nutritional disorder globally and often occurs without anemia, especially in women of reproductive age. Conventional screening practices that rely solely on hemoglobin levels may miss a significant number of cases. Aim: To determine the frequency of iron deficiency in non-pregnant females having normal hemoglobin levels, and to identify associated risk factors based on clinical, demographic, dietary, and reproductive variables. Methodology: A cross-sectional study was conducted at the Department of Medicine, Services Hospital Lahore, over a period of six months. A total of 100 non-pregnant females aged 16–45 years with hemoglobin >11 g/dL were enrolled using non-probability consecutive sampling. Data on sociodemographic, clinical, dietary, and reproductive factors were collected. Laboratory evaluation included hemoglobin, serum ferritin, and serum iron. Iron deficiency was defined as serum ferritin <15 µg/L and serum iron <10 µmol/L. Data were analyzed using SPSS v25, and associations were tested using Chi-square test and odds ratios; p < 0.05 was considered statistically significant. Results: Iron deficiency was found in 41% of participants despite normal hemoglobin levels. Significant associations were observed between iron deficiency and underweight BMI (OR = 7.11, p = 0.002), history of anemia (OR = 6.30, p = 0.001), hypertension (OR = 3.84, p = 0.012), ≥2 deliveries (OR = 3.10, p = 0.012), breastfeeding (OR = 2.50, p = 0.045), sedentary lifestyle (OR = 2.41, p = 0.049), no supplement use (OR = 2.80, p = 0.034), and low meat intake (OR = 3.06, p = 0.016). The strongest predictors were low serum ferritin (OR = 9.47, p < 0.001) and low serum iron (OR = 5.54, p < 0.001). Conclusion: A considerable proportion of non-pregnant females with normal hemoglobin levels were found to be iron deficient, highlighting the inadequacy of hemoglobin-based screening. Risk factors were multifactorial, involving nutritional, reproductive, and behavioral dimensions. Routine biochemical screening and broader nutritional interventions are recommended to detect and manage iron deficiency in at-risk non-pregnant females, even in the absence of anemia.